Technological developments of Japanese prefabricated housing in an early stage. Issue 1 (14th October 2018) - Matsumura, Shuichi; Gondo, Tomoyuki; Sato, Kouichi; Morita, Yoshiro; Eguchi, Toru
Abstract: Major prefabricated housing manufacturers started their business in the 1960s and became world‐class large housing companies. This study clarifies the early stages of development in 9 major prefabricated housing manufacturers based on interviews with their in‐house engineers and architectural designers as well as through the analysis of related documents. Early prefabricated houses were developed intensively by a small number of engineers. Various architectural styles and specialists, including foreign architecture, famous architects and academics, affected some aspects of these developments. Furthermore, each of the early prefabricated houses had many unique building system characteristics. Some of these characteristics were modified in the early stages of development, while others still remain today. Abstract : Major Japanese prefabricated houses manufacturers started their business around 1960s and became world class large housing companies. This study clarifies 9 major prefabricated houses manufacturers' developments or features of building systems at early stages by interviews with their in‐house engineers and architectural designers as well as analysis of relating documents.